New-onset dermatomyositis following COVID-19: A case report - Shimizu, Hiroshi; Matsumoto, Haruki; Sasajima, Tomomi; Suzuki, Tomohiro; Okubo, Yoshinori; Fujita, Yuya; Temmoku, Jumpei; Yoshida, Shuhei; Asano, Tomoyuki; Ohira, Hiromasa; Ejiri, Yutaka; Migita, Kiyoshi (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Most of the infected individuals have recovered without complications, but a few patients develop multiple organ involvements. Previous reports suggest an association between COVID-19 and various inflammatory myopathies, in addition to autoimmune diseases. COVID-19 has been known to exacerbate preexisting autoimmune diseases and trigger various autoantibodies and autoimmune disease occurrence. Here we report a case of complicated COVID-19 with anti-synthetase autoantibodies (ASSs) presenting with skin rash, muscle weakness, and interstitial lung disease (ILD) and subsequently diagnosed with dermatomyositis (DM). A 47-year-old Japanese male patient without any previous history of illness, including autoimmune diseases, presented with a high fever, sore throat, and cough. Oropharyngeal swab for SARS-Cov-2 polymerase chain reaction tested positive. He was isolated at home and did not require hospitalization. However, his respiratory symptoms continued, and he was treated with prednisolone (20 mg/day) for 14 days due to the newly developing interstitial shadows over the lower lobes of both lungs. These pulmonary manifestations remitted within a week. He presented with face edema and myalgia 4 weeks later when he was off corticosteroids. Subsequently, he presented with face erythema, V-neck skin rash, low-grade fever, and exertional dyspnea. High-resolution computed tomography of the chest showed ILD. Biochemical analysis revealed creatine kinase and aldolase elevations, in addition to transaminases. Anti-aminoacyl tRNA synthetase (ARS) was detected using an enzyme-linked immunosorbent assay (170.9 U/mL) (MESACUP™ (Medical & Biological Laboratories, Japan), and the tRNA component was identified as anti-PL-7 and anti-Ro-52 antibodies using an immunoblot assay [EUROLINE Myositis Antigens Profile 3 (IgG), Euroimmun, Lübeck,Germany]. The patient was diagnosed with DM, especially anti- synthase antibody syndrome based on the presence of myositis-specific antibodies, clinical features, and pathological findings. The present case suggests that COVID-19 may have contributed to the production of anti-synthetase antibodies (ASAs) and the development of de novo DM. Our case highlights the importance of the assessment of patients who present with inflammatory myopathy post-COVID-19 and appropriate diagnostic work-up, including ASAs, against the clinical features that mimic DM after post-COVID-19.